2015
DOI: 10.1289/ehp.1408579
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Toxicity of a Mixture of Regulated Drinking-Water Disinfection By-Products in a Multigenerational Rat Bioassay

Abstract: BackgroundTrihalomethanes (THMs) and haloacetic acids (HAAs) are regulated disinfection by-products (DBPs); their joint reproductive toxicity in drinking water is unknown.ObjectiveWe aimed to evaluate a drinking water mixture of the four regulated THMs and five regulated HAAs in a multigenerational reproductive toxicity bioassay.MethodsSprague-Dawley rats were exposed (parental, F1, and F2 generations) from gestation day 0 of the parental generation to postnatal day (PND) 6 of the F2 generation to a realistica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 21 publications
1
21
0
Order By: Relevance
“…57 However, a recent study evaluated the toxicity of a DBP mixture in a multigenerational bioassay in rats and observed no adverse effects on fertility, pregnancy maintenance, prenatal or postnatal survival, and birth weights. 58 Collectively, these data highlight the need for in depth studies on reproductive toxicity of DBPs and their biological mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…57 However, a recent study evaluated the toxicity of a DBP mixture in a multigenerational bioassay in rats and observed no adverse effects on fertility, pregnancy maintenance, prenatal or postnatal survival, and birth weights. 58 Collectively, these data highlight the need for in depth studies on reproductive toxicity of DBPs and their biological mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Endocrine disruptors are capable of altering neural transmission and the formation of neural networks (Kajta and Wójtowicz, 2013). Animal studies, using artificial mixtures of DBPs detected in drinking water, observed endocrine disrupting effects, but these effects were not found when using trihalomethanes or haloacetic acids alone (Narotsky et al, 2015(Narotsky et al, , 2013. Thus, the driving agents of the DBP mixture toxicity and implicated mechanisms remain an active area of investigation (Plewa et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In this issue of EHP , investigators assess the reproductive toxicity of a mixture of chlorination DBPs in rats. 2 …”
mentioning
confidence: 99%
“…7 Rather than setting maximum contaminant levels for individual chemicals, the agency regulates total THMs and total HAAs. 2 …”
mentioning
confidence: 99%
See 1 more Smart Citation